Analyzing Risk Factors for Schizophrenia: Genetic Aspects to Environmental Influences: A Literature Review - Shafira, Aisyah Nur Shafira; Fahma, Hilmia (Journal of Diverse Medical Research: Medicosphere, 2025)
Abstract Background. Schizophrenia is a complex and multifactorial mental disorder, influenced by the interaction between genetic and environmental factors. This study aims to analyze the risk factors for schizophrenia from genetic aspects to environmental influences. Methods. used in writing this scientific article, as for some of the steps used, is a literature search strategy, then data collection. Discussion. genetic factors, such as family history, have a significant influence on the risk of schizophrenia. In addition, environmental factors such as psychosocial stress, psychoactive substance use, and socioeconomic conditions also contribute to the development of this disorder. That the combination of genetic predisposition and environmental stressors can increase an individual's vulnerability to schizophrenia. Conclusions. of this study emphasize the importance of comprehensive interventions, including primary prevention aimed at high-risk individuals. Efforts to increase public awareness of schizophrenia risk factors and stress management strategies may help to reduce the incidence of this disorder. Further research is needed to explore the relationship between these factors and the underlying biological mechanisms. Keywords. Schizophrenia; Risk Factors